Relationship of genotypes of csn2 gene in milk production and proportions of its components in Holstein Friesian cows bred in Iraq (Texas Journal of Agriculture and Biological Sciences, 2023)
The study was conducted on 50 Holstein cows of different ages and weights raised in Iraq at the Taj AlNahrain cattle station in the Al-Qadisiyah governorate. The DNA was extracted, and its purity was examined in the Molecular Genetics Laboratory at the College of Agriculture, University of Basrah. The study was conducted from 12.03.2022 to 03.02.2022. Milk and blood samples were taken during this period, and the DNA was extracted and sent to China. In order to know the genotypes of the CSN2 milk protein gene and its relationship to the product characteristics and composition of milk. The study showed that when a piece of the CSN2 gene was amplified, three genotypes were obtained and that the second pattern differs from the first and third patterns by the nitrogenous base of sequence 88. The base shifted from A to C, and the third pattern differs from the first and second patterns by changing the nitrogenous base of the sequence 52, as it shifted from C to T without changing the amino acid sequence of the gene, and the distribution of the patterns among the study cows was 23 for the first pattern, 10 for the second pattern, and 17 for the third pattern. There were significant differences (P≤0.01) between the genotypes of the CSN2 gene in milk production, where the first individual genotype was superior to the second and third in daily, weekly and monthly milk production and the production of the first stage, as well as a significant effect (P≤0.01) of the genotypes of the CSN2 gene on the components of Milk (protein and fat), where the second and third individual of the CSN2 gene outperformed the first individual.